Biointegrative Nail Raftering Improves Pain and Function in Patients With Subchondral Insufficiency of the Knee - Alexander C. Weissman, M.S.; Allen A. Yazdi, B.S.; Jared P. Sachs, M.S.; Sarah A. Muth, B.A.; Andrew S. Bi, M.D.; Ron Gilat, M.D.; Brian J. Cole, M.D., M.B.A. (Arthroscopy, Sports Medicine, and Rehabilitation)
Purpose: To evaluate the utility of implanting biointegrative cannulated nails in a rafter arrangement within the tibial plateau or femoral condyle for treatment of subchondral insufficiency of the knee. Methods: Patients were followed for 12 months after surgical intervention for subchondral insufficiency using biointegrative, fiber-reinforced fixation nails. Patients (ages 18-75 years) had moderate knee pain for at least 6 months, unicompartmental Kellgren-Lawrence grade 2-3 and bone marrow lesions confirmed on magnetic resonance imaging (MRI). Comparison of baseline and postoperative Knee Injury and Osteoarthritis Outcome Score (KOOS) was the primary outcome measure. Other patient-reported outcome measures included International Knee Documentation Committee (IKDC) and Patient-reported Outcomes Measurement Information System (PROMIS). Minimal clinically important difference was calculated for each PRO. Calculated bone marrow lesion volumes measured on MRI were compared from baseline to 12 months postoperative. Results: Nine patients were included, with follow-up of 12 ± 1 months. Significant improvements were seen in KOOS, IKDC, PROMIS, and Veterans RAND 12-Item Health Survey (VR-12). The average change in patient-reported outcome measures at 12 months were KOOS (19.68, P = .008), IKDC (28.99, P = .004), PROMIS Pain Interference (10.35, P = .008), PROMIS Physical Function (11.06, P = .008), and VR-12 Physical (16.14, P = .008). Minimal clinically important difference was achieved in 89% of patients for KOOS, 100% for IKDC, 87.5% for PROMIS Pain Interference and Physical Function, and 62.5% for VR-12 Physical. The average decrease in subchondral lesion size measured on MRI did not reach statistical significance (P = .064). All patients reported successful return to sport, with no reoperations or implant failures. Conclusions: Biointegrative fixation nail raftering for treatment of subchondral insufficiency of the knee resulted in improved patient-reported pain and functionality at 12-month follow-up in the setting of early-to-moderate osteoarthritis. Level of Evidence: Level IV, therapeutic case series.